Sonates pour le pianoforte á deux mains : op. 7 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Leipzig; Gustav Heinze; Germany, 2025)
Separate issue of the Piano sonata no. 4 in E-flat major, op. 7, published in Leipzig by Gustav Heinze as an "edition nouvelle et soigneusement revue," reprinted from the plates of Stern & Cie. in Berlin.